Molecular Advancements Establishing Chlamydomonas as a Host for Biotechnological Exploitation - Schroda, Michael; Remacle, Claire (Frontiers in Plant Science, 2022)
Chlamydomonas reinhardtii is emerging as a production platform for biotechnological purposes thanks to recent achievements, which we briefly summarize in this review. Firstly, robust nuclear transgene expression is now possible because several impressive improvements have been made in recent years. Strains allowing efficient and stable nuclear transgene expression are available and were recently made more amenable to rational biotechnological approaches by enabling genetic crosses and identifying their causative mutation. The MoClo synthetic biology strategy, based on Golden Gate cloning, was developed for Chlamydomonas and includes a growing toolkit of more than 100 genetic parts that can be robustly and rapidly assembled in a predefined order. This allows for rapid iterative cycles of transgene design, building, testing, and learning. Another major advancement came from various findings improving transgene design and expression such as the systematic addition of introns into codon-optimized coding sequences. Lastly, the CRISPR/Cas9 technology for genome editing has undergone several improvements since its first successful report in 2016, which opens the possibility of optimizing biosynthetic pathways by switching off competing ones. We provide a few examples demonstrating that all these recent developments firmly establish Chlamydomonas as a chassis for synthetic biology and allow the rewiring of its metabolism to new capabilities.